2005
DOI: 10.2337/diabetes.54.3.906
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association Between a Lymphoid Tyrosine Phosphatase (PTPN22) and Type 1 Diabetes

Abstract: The lymphoid-specific phosphatase (LYP) encoded by PTPN22 is involved in preventing spontaneous T-cell activation by dephosphorylating and inactivating T-cell receptor-associated Csk kinase. We have genotyped 396 type 1 diabetic patients and 1,178 control subjects of Caucasian descent from north central Florida and report a strong association between type 1 diabetes and a polymorphism (R620W) in the PTPN22 gene. The homozygous genotype for the T allele encoding the 620W residue is associated with an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 17 publications
6
80
1
1
Order By: Relevance
“…25 Similar to the above-summarized murine model, an increased germinal center formation is observed in autoimmune models of pSS, SLE, and T1D. 26,27 As previously shown by others, 11,[28][29][30][31][32][33] our results disclosed that T allele is a risk factor for T1D (OR ¼ 1.83), although this difference was in the threshold of significance (P ¼ 0.06).…”
Section: Resultssupporting
confidence: 81%
“…25 Similar to the above-summarized murine model, an increased germinal center formation is observed in autoimmune models of pSS, SLE, and T1D. 26,27 As previously shown by others, 11,[28][29][30][31][32][33] our results disclosed that T allele is a risk factor for T1D (OR ¼ 1.83), although this difference was in the threshold of significance (P ¼ 0.06).…”
Section: Resultssupporting
confidence: 81%
“…Stimulation of peripheral blood mononuclear cells (PBMCs) from people at increased risk of T1D with an overlapping panel of synthetic peptides from the T1D-associated autoantigen glutamate decarboxylase (GAD) [27] identified a major determinant (amino acids 247-279) that had significant sequence similarity to the P2-C protein of Coxsackie B virus, which had been previously associated with the onset of T1D [28]. Furthermore, PBMC from individuals responding to GAD peptides also responded to a Coxsackie P2-C peptide (amino acids [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Rudy et al (1995) [29] subsequently identified a 13 amino acid peptide of another T1D-associated autoantigen, proinsulin (amino acids [24][25][26][27][28][29][30][31][32][33][34][35][36] [30], which bears marked similarity to a peptide of GAD65 (amino acids 506-518).…”
Section: Familial Risk Of Type 1 Diabetesmentioning
confidence: 99%
“…A nonsynonymous SNP at position 1858 of PTPN22 was reported to be associated with T1D in many populations (OR for the heterozygous C/T genotype was 1.7) [40][41][42][43][44][45]. This C1858T SNP resulted in a missense mutation in people bearing the T1D risk allele that changed an arginine to a tryptophan at position 620 (R620W), resulting in the inability of LYP to bind its signaling molecule CSK [46], which increases phosphatase activity.…”
Section: Ptpn22mentioning
confidence: 99%
“…The identification of PTPN22 1858 C/T as a putative disease risk allele in type 1 diabetes (T1D) [1][2][3][4][5][6] and subsequently RA [7][8][9] and other autoimmune diseases including SLE, 10,11 Graves disease 12 and JIA 9 has engendered considerable excitement. 13 PTPN22 also known as LYP (lymphocyte phosphatase) encodes a hematopoietic tissue-specific protein tyrosine phosphatase that is thought to inhibit T-cell activation through its association with the Csk tyrosine kinase.…”
mentioning
confidence: 99%